Childhood's end adaptation : the control of technology : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, Wellington, New Zealand - Vegar, Ivan (Massey University, 2019)
Concept design can communicate a cinematic allegory that enables an audience to understand a visual representation of the Faustian bargain, as technological advancement. This visualisation demonstrates how advanced technology can bestow power, at the cost of our free will. Humans have an instinctive need to explore and solve everyday challenges and we often do this through technology. It is a pivotal aspect to our purpose in life, defining our humanness and a crucial reason for why we are perceived as the dominant species on the planet. Yet in contemporary society we are so heavily dependent on technology we often don’t ask who is really in control? Using Childhood’s End, by Arthur C. Clark as a narrative precedent, this research will explore the Faustian bargain through a series of key-scene designs. The research results in an adaptation for a hypothetical feature film, that intends to use key-scene design to warn audiences that the price of technological advancement is often the abdication of control. The final designs are informed by principals of futurology, technocracy and astronomy, as an advocate of the adaptation of the novel’s story with core themes as the author intended. This research intends to enable the visual design of a narrative which informs and provokes technological thought in audiences but also respects the source material. Characters, props and environments are used to demonstrate how to design content that challenges our role as the dominant sentient species, both through how we relinquish our ability to explore new frontiers, and how advanced alien technology is represented.
Keywords: 330316 Visual communication design (incl. graphic design)